Discerning The True Nature of Servant Hood in The Seal of Prophets: Lesson for Muslims - Jimoh Muhammad, Usman; Hunkuyi, Ibrahim Lawal (Research and Community Service Institute (LP2M) of Institute Pesantren Sunan Drajat, 2025)
The paper acknowledges the supremacy of the Creator over the creation and emphasises the need to understand the true nature of servant hood as exemplified by the Seal of Prophets, Prophet Muhammad (peace be upon him). Furthermore, it presents the Noble Prophet as the ultimate model of servant hood in the sight of Allah and a perfect example for mankind. Drawing on relevant examples, the paper discusses his self-declaration of servant hood, his devotion to the creator despite divine reassurance, his pardon for people on personal grievances and his embrace of an ascetic lifestyle despite his capability to attain material wealth for himself and his family. The paper highlights his commitment to Noble conduct and his rejection of undesirable attitude. It concludes that the Noble Prophet Muhammad (peace be upon him), has embodies the ideal servant of Allah. The paper recommends Muslims to study his life deeply in order to understand the principles of servant hood and apply them in their daily activities.